Fair Pricing in Multicultural Societies: Ibn Taymiyah's Islamic Economic Principles for Inclusive Commerce - Purwanto, Andi; Mugiyati, Mugiyati (Kawanua International Journal of Multicultural Studies, 2025)
Islam was revealed by Allah SWT to regulate all forms of human behavior in relation to other humans to meet the needs of their lives in the world. This includes principles that govern economic turnover. In this case, one of the Islamic intellectuals, Ibn Taymiyah, has an interest in conceptualizing the economy through the Islamic religious approach. As for this study, using descriptive qualitative research, the researcher directly researched the books of Ibn Taimiyah and several other supporting literature. In this study, the researcher found that there are several concepts about Islamic economics, namely fair prices, and price regulations that have several clear divisions in accordance with the concept of Islamic economics according to Ibn Taymiyah